Film condensation in horizontal circular section microchannels. (3rd August 2009) - Wang, Hua Sheng; Rose, John W.
Condensation of R134a in horizontal circular section microchannels is investigated theoretically. The model takes account of surface tension, vapour shear stress and gravity. The case considered here is where the channel wall temperature is uniform and the vapour is saturated at inlet. The tube diameter varies in the range of 0.5-5 mm and the mass velocity varies in the range of 100-1, 300 kg/m² s. The local condensate film profile around the cross-section is calculated together with the mean heat-transfer coefficient at different distances along the channel. Results show that the enhancing effect of surface tension in circular section microchannels is small compared to that in non-circular section microchannels.